Deep hydrothermal fluid–rock interaction: the thermal springs of Da Qaidam, China. Issue 4 (4th October 2016) - Stober, I.; Zhong, J.; Zhang, L.; Bucher, K.
Abstract: Hot water flows from springs along the border fault system at the SW rim of the Qilian Mountains near the city of Da Qaidam (Qinghai Province, Western China). The outflow temperature is close to 72°C, and the clear water contains about 1.4 g l −1 total dissolved solids. The water contains predominantly Na and Cl, and significant and equal amounts of hydrogen carbonate and sulfate. The water originates from a fractured granite reservoir at about 5 km depth, suggested by the estimated Qtz and Na–K equilibrium temperatures of 130–150°C. The solutes are derived from the interaction of the deep ground water with the solids of the fractured granite. However, the high Cl/Br mass ratio of about 550 in the deep water and the composition of surface runoff suggest the presence of an additional evaporite component introduced by surface infiltration. The source of this surface component is probably eolian deposits of halite, gypsum, and borate minerals from the salt flats and deserts of the Qaidam Basin on the slopes of the Qilian Mountains. The deep hydrothermal flow system is topography driven, and the upwelling water is focused and channeled to the damage zone of the Qilian border fault.